When Heat Becomes a Risk: The Impact of Heatwaves on Hypertension - A Systematic Review - Czajkowski, Mateusz; Dryl-Jarmoc, Ewa; Ślinko, Izabela; Kuliś, Gabriela; Panas, Zuzanna; Krawczuk, Kacper; Dziemiańczuk , Jakub; Zimowski, Mateusz; Kadysz, Piotr; Kolanek, Agata (Quality in Sport, 2026)
Introduction:Hypertension is considered one of the most common chronic diseases affecting over 30 % of the population of adults in the world. Also is the most important modifiable risk factor for cardiovascular disease(CVD). Heatwaves, defined as periods of extremely high temperatures lasting at least 2–3 days, pose a growing threat to public health amid climate change. The climate is changing, and simultaneously leading to a higher frequency of extreme weather events, including heatwaves. The impacts of heatwaves on human health and their underlying mechanisms, particularly regarding the cardiovascular system, are well-known. Heatwaves can impact blood pressure and control of hypertension through many different mechanisms. This paper aims to review the relationship between heatwaves and hypertension, including incidence, blood pressure variability, and cardiovascular outcomes. Materials and methods: A review of selected literature in the PubMed, Scopus, and ScienceDirect for studies published between 1990 and 2026.Conclusions:The rise of heatwaves as an increasingly concerning environmental issue, that can affect cardiovascular health will contribute to blood pressure regulation. Heat causes vasodilation initially, but there are compensatory mechanisms like dehydration, activation of the sympathetic nervous system, hormonal response which will result in transiently elevated blood pressure, and increased risk for cardiovascular events. Despite mounting research evidence, the link between heatwaves and the development of hypertension is poorly understood, current literature contains limited heterogeneous data on this topic. Additional research is needed to evaluate whether heatwaves act as a causal or triggering agent to cause dysregulation of blood pressure in order to develop effective public health interventions.